Patients' satisfaction: The medical appointments valence in Portuguese public hospitals. (October 2018) - Ferreira, D.C.; Marques, R.C.; Nunes, A.M.; Figueira, J.R.
Highlights: We study the patients' satisfaction concerning the medical appointments valence in Portuguese hospitals. We investigate the relative weights patients attribute to each criterion and subcriterion from Donabedian's triad. We use the MUSA method and Kano's model to classify those criteria and subcriteria. We study the improvement and the applicable strategies to enhance the performance of each criterion and subcriterion. We provide some policy implications and concerns in line with the results. Abstract: Measuring patients' satisfaction in secondary health care-based medical appointment services is a rarely addressed, though a very important, task. In general, this task is devoted to the emergency room. Improving (other) areas where patients are mostly dissatisfied assumes a relevant role since in Beveridge-based health systems providers are mainly financed through taxes. This paper aims to evaluate the satisfaction of Portuguese patients with reference to the national health system and public hospital medical appointment services, as well as to identify main priority areas of low performance. Data is collected from a report created and made available overtly by an official entity, managed by the Ministry of Health. Data consists of frequencies of patients assessing their own satisfaction (in four levels) regarding a set of seven criteria, five of them split into several subcriteria. These ones were selected based on their availability, suitability, and the literature review, and aimed to characterize the hospitals' medical appointments valence concerning their image, cleanliness, facilities quality, technological progress, staff professional competence and care, as well as the waiting time in different stages before and after the medical appointment. This paper makes use of the so-called Multicriteria Satisfaction Analysis (MUSA) method, which is a very useful linear programming model developed and used with the intention of analyzing customer satisfaction and identifying priorities to improve the provider's performance. Since data consists of frequencies in four satisfaction levels for a set of criteria and subcriteria, simulated patients were used based on a bootstrap-based technique, admitting independence between criteria/subcriteria. MUSA results allow the clustering of criteria according to Kano's model and its refined version (must-be, one-dimension and attractive requirements), upon which satisfaction improving strategies must be formulated. Accordingly, the model identifies the waiting time (at any stage) as one of the most critical areas requiring enhancements. This is an expected outcome as these criteria corroborate the highest patients' dissatisfaction scores.